The Ins and Outs of German Unemployment - Carsten Ochsen (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2015)
This paper analyzes the contribution of flow rates and flow probabilities for unemployment dynamics of different age groups using administrative panel data for Germany. I consider a three-state model and allow for flows from/to inactivity (out of the labor force) to/from unemployment. The dynamics that arise from the inactivity and activity flows account for about 40% of unemployment dynamics (inactivity is more important), while the contribution of separation and job finding is roughly 40% and 20% respectively. Across five age cohorts I find remarkable differences in flow contributions. In the steady state approach the overall contribution of inflow and outflow rates is roughly 50%:50%, but for the non-steady state approach I find a slightly stronger contribution of the outflow rates. I also point out the possibility of a regional aggregation bias that can be of similar importance as the time aggregation bias.
Keywords: J63; J64; J10; 330